Optimization of Oyster Mushroom Dough Mixing Machine Using Omron CP1E PLC Control - Rahmat, Saepul; Sumardiono, Arif; Purwiyanto (Jurusan Teknik Elektro, Universitas Bangka Belitung, 2026)
Oyster mushroom cultivation is vital for providing the growing medium. Manually mixing the growing medium has several limitations, including time-consuming and inconsistent results. This paper objectives are to resolve growing medium oyster mushroom with mixing machine based on the Omron CP1E Programmable Logic Controller (PLC). The research methodology of mechanical and electrical of the machine was equipped with a single-phase AC motor, relay, control panel, and PLC-based control system to increases labor efficiency and ensures uniformity in the media mixture. This paper contribution research are to find the best composition of ingredients with PLC control to get homogenous media mixture by measuring the weight of the ingredients, mixing time, power consumption, and the homogeneity of the mixture. Based on the test results, the prototype is able to pack oyster mushroom growing media close to the initial mass, which is around 2975–3015 grams with an error of 1%, as well as decreasing power consumption due to the growing media mixture starting to become homogeneous so that the motor works lighter. The prototype of the oyster mushroom mixing machine has been successfully mix the media homogenous in 3minutes with the motor speed 70 rpm and power consumption 345 Watt.